THE CONCEPT OF LABOR MIGRATION AND MIGRATION POLICY: ESSENCE AND CONTEMPORARY INTERPRETATION. - Tulkin Chulliev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The philosophical underpinnings and contemporary interpretations of labor migration and migration policy are examined in this essay. With a focus on the extraordinary importance of migration in the 20th century, it starts by examining the historical relevance of labor mobility as a transformational factor in demographic, economic, and political development. The study then looks at the current causes of labor migration, such as wage disparities, labor market imbalances, and global economic integration. The multiple effects of labor migration on sending and receiving nations are particularly highlighted, along with the ways in which it promotes social transformation, skill transfer, and economic progress.